Socio-economic impact of adverse working conditions and their differentiation - E. V. Bakiko; V. S. Serdyuk; E. V. Yakovleva (Омский научный вестник: Серия "Общество. История. Современность")
One way to motivate employers to improve occupational safety is to assess the socio-economic consequences of the conditions and occupational safety in the organization. The work presents the results of differential analysis of the components of socioeconomic consequences of unfavourable working conditions at economic facilities. The method of integral evaluation obtained values of direct and indirect damage from unfavourable working conditions on the example of a number of enterprises of Russia. The ratios of damage and the amount of underestimation by employers of their consequences are shown